Vers une digestibilite absolue de Leucaena chez les ruminants? - Chater, S. (1986)
Reviews work on rumen bacteria that appears to solve the problem of mimosine-DHP toxicity, which currently prevents feeding of the tree foliage of Leucaena Leucocephala in large quantities for ruminant livestock.